Competencias matemáticas en la enseñanza media - Barrantes Campos, Hugo (2010)
In this work, a discussion is realized about the concept of competence and, particularly, of mathematical competence. Some mathematical competences that have been proposed for Secondary School (grades 7-9) are described. Also, some implications of the competences approach are analyzed. Finally, the mathematics study program for the III cycle of the Costa Rican General Basic Education is analyzed regarding the Students competences pretended to be developed.